Drinking Through Good Times and Bad: The Role of Consumer Differences. (August 2021) - Joo, Hailey Hayeon; Kim, Minki; Lee, Jungmin; Chintagunta, Pradeep
The authors revisit the question of alcohol consumption and public health over business cycles by decomposing overall alcohol consumption into drinking frequency and intensity in relation to consumer heterogeneity. To study this question, they use consumer-level panel data on the reported consumption (not purchases) of beer, which is the most heavily consumed alcoholic beverage and accounts for the majority of binge drinking in the United States. Leveraging the panel nature of the data, the authors find a negative (positive) relationship between unemployment and drinking frequency (intensity). Total consumption, which is the product of drinking frequency and intensity, is procyclical. To uncover differences in behavior across consumers and to provide policy recommendations at a segment level, the authors present a structural model where consumers simultaneously choose the frequency and intensity of their alcohol consumption. They find differences across consumers in their behaviors, notably with respect to income and age. They conduct policy simulations to compare the effectiveness of alcohol-related policies to counter the adverse effects of recessions on the health of vulnerable groups such as low-income and elderly populations.